Investment Decisions And The Factors That Affect Them - Mardiatun Ramadhani Purba; Debbi Cynthia Ovami; Haidir Lubis (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2023)
This research aims to analyze the factors that influence company investment decisions. This research is quantitative research using statistics. The statistics used can be descriptive and inferential/inductive statistics. Data collection techniques use secondary data obtained from the publication of financial reports on mining companies on the Indonesia Stock Exchange. Data analysis techniques were carried out to determine the influence of the relationship between independent variables on the dependent variable using simple linear regression analysis. Data management is carried out with the help of application programs computer SPSS 22 for windows. The research results found that where the significance level is greater than 0.05, which means Ha is rejected, so it can be said that cash flow,leverage, liquidity, sales growth and company size do not influence simultaneously. Thus, the Ha hypothesis6 which states that cash flow,leverage, liquidity, sales growth and company size have no influence on investment decisions and are rejected.